We are experiencing a slight delay : tips, tales, travels - Janetti, Gary (Harper, an imprint of HarperCollinsPublishers, 2024)
"In this hilarious and often touching collection, the New York Times bestselling author, television writer, and producer takes us with him on travels across the globe"--